Show the Step-by-Step Solution to the Equation

Algebra
Tutor: None Selected Time limit: 1 Day

Please explain the steps to the problem.

6(-t+1)-4(2t-1)=t+4-5t

Sep 6th, 2014

6(-t+1)-4(2t-1)=t+4-5t

-6t + 6 - 8t + 4 = t + 4 - 5t

-14t + 10 = 4 - 4t

14t - 4t = 10 - 4

10t = 6

t = 6/10

t = 3/5


Sep 6th, 2014

Studypool's Notebank makes it easy to buy and sell old notes, study guides, reviews, etc.
Click to visit
The Notebank
...
Sep 6th, 2014
...
Sep 6th, 2014
May 26th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer